1992
DOI: 10.1107/s0021889892005053
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction of bent crystals in Bragg geometry. I. Perfect-crystal modelling

Abstract: X-ray reflectivity, widths, centroid shifts and profiles for curved perfect crystals are calculated from a model. The crystal is approximated by a stack of perfectcrystal lamellae or blocks with a gradually changing (mean) orientation. A computer program has been developed to calculate the above quantities in the Johann geometry for the composite crystal from the dynamic theory of diffraction. Focusing and defocusing aberrations and the use of photographic detection methods are included. Correction of omission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Earlier work [8,[13][14][15] demonstrated that a thorough understanding of diffraction conditions, dispersion relations and source systematics can allow the determination of transition energies in highly charged ions to a precision limited by statistics [5,16].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier work [8,[13][14][15] demonstrated that a thorough understanding of diffraction conditions, dispersion relations and source systematics can allow the determination of transition energies in highly charged ions to a precision limited by statistics [5,16].…”
mentioning
confidence: 99%
“…Because inner shell neutral atomic lines are asymmetric due to underlying atomic processes [19,20], an extensive investigation of Kα peak shapes was undertaken to provide a robust fitting procedure [21] to accurately determine peak profile turning points as well as modelling the doublet as the sum of six Voigt functions. Finally, diffraction angles and detector positions were calculated using a curved crystal dynamical diffraction modelling code [13,14] to determine photon energy as a function of photon diffraction angle and detector position. Figure 1 shows the fitted helium-like Ti spectrum accumulated over several days of experimentation and weeks of calibration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the assumptions of this method is in (Caciuffo et al, 1987) and (C.T. Chantler, 1990) and a good validation with experiments is in (Erola et al, 1990) …”
Section: Figurementioning
confidence: 99%
“…When labelling a spectral line with a diffraction angle one must consider a modified Bragg law. Curved crystal diffraction modelling code (Chantler, 1992) allows us to quantify and reduce uncertainties of order 200 ppm in the dispersion function determination to around 5 ppm. It is not uncommon for published experimental results to contain no mention of uncertainties due to the spectrometer system used.…”
Section: Systematicsmentioning
confidence: 99%